Graphical functions with spin - Oliver Schnetz (Journal of High Energy Physics)
Abstract The theory of graphical functions is generalized from scalar theories to theories with spin, leading to a numerator structure in Feynman integrals. The main part of this article treats the case of positive integer spin, which is obtained from spin 1/2 theories after the evaluation of γ traces. As an application (in this article used mainly to prove consistency and efficiency of the method), we calculate primitive Feynman integrals in Yukawa-ϕ 4 (Gross-Neveu-Yukawa) theory up to loop order eight.